Genotoxic impact of aluminum-containing nanomaterials in human intestinal and hepatic cells. (February 2022) - Jalili, Pégah; Huet, Sylvie; Burel, Agnès; Krause, Benjamin-Christoph; Fontana, Caroline; Chevance, Soizic; Gauffre, Fabienne; Guichard, Yves; Lampen, Alfonso; Laux, Peter; Luch, Andreas; Hogeveen, Kevin; et al.
Abstract: Exposure of consumers to aluminum-containing nanomaterials (Al NMs) is an area of concern for public health agencies. As the available data on the genotoxicity of Al2 O3 and Al 0 NMs are inconclusive or rare, the present study investigated their in vitro genotoxic potential in intestinal and liver cell models, and compared with the ionic form AlCl3 . Intestinal Caco-2 and hepatic HepaRG cells were exposed to Al 0 and Al2 O3 NMs (0.03 to 80 μg/cm 2 ). Cytotoxicity, oxidative stress and apoptosis were measured using High Content Analysis. Genotoxicity was investigated through γH2AX labelling, the alkaline comet and micronucleus assays. Moreover, oxidative DNA damage and carcinogenic properties were assessed using the Fpg-modified comet assay and the cell transforming assay in Bhas 42 cells respectively. The three forms of Al did not induce chromosomal damage. However, although no production of oxidative stress was detected, Al2 O3 NMs induced oxidative DNA damage in Caco-2 cells but not likely related to ion release in the cell media. Considerable DNA damage was observed with Al 0 NMs in both cell lines in the comet assay, likely due to interference with these NMs. No genotoxic effects were observed with AlCl3 . None of the Al compounds induced cytotoxicity, apoptosis, γH2AX or cell transformation. Highlights: Al 0 and Al2 O3 NMs did not induce chromosomal damage in the micronucleus assay. Al 0 interference was observed in the comet assay. Al2 O3 induced DNA damage in the Fpg-modified comet assay although no significant ROS increase was observed.